?HEAVY METAL IONS CONCENTRATION IN WHEAT PLANT (TRITICUM AESTIVUM L.) IRRIGATED WITH CITY EFFLUENT - Farid, Sajid (Biological Sciences - PJSIR, 2003)
Pakistan lies under arid and semi arid zones. There is shortage of water for irrigation. Farmers near being cities raise crops by diverting the city effluent towards their fields. It contains heavy toxic metal ions like cadmium, chromium, cobalt and nickel, which may accumulate in the edible portion of crops and cause clinical problems to human being. The concentration of metal ions in the effluent and effluent irrigated wheat (Triticum aestivum L.) was determined by Atomic Absorption Spectrophotometer. Heavy metal ions (Cd, Cr and Co) mean concentrations were found above the permissible limits recommended for irrigation water. In the grains of wheat plant concentration of Cd, Cr and Co was found above the permissible levels recommended by World Health Organization (WHO) for foodstuff.